Rheological study of hydrogel - Xu, Wei (2015)
This project aims to investigate the rheological behavior of a hydrogel to understand how the hydrogel is formed though from a rheological point of view. It was prepared to study the rheological behavior that a nanocomposite hydrogel based on the combination of κ-carrageenan and nanoparticles (nanosilica and graphene oxide [GO]). I performed a temperature sweep test at small amplitude of oscillatory shear measurements to investigate the effect of nanosilica and GO nanoparticles on the gel properties, as functions of κ-carrageenan concentration and nanoparticles load. The result showed that silica and GO were able to impair the gelation process of κ-carrageenan. It was observed to weaken the gel strength to add certain loads of nanosilica and GO nanoparticles to the κ-carrageenan gel as suggested by the decrease in the viscoelastic moduli( G’,G’’) of the gel and of the gelation & melting temperature. This weakening effect was slightly more marked as more nanoparticles were involved. These results indicate that the nanoparticles function as physical barriers to polysaccharide chain’s aggregation and gelation. However, at higher particle loads in the high concentration κ-carrageenan gel, gel strength do not weaken steeply as compared to the lower particle loads, but remain unchanged with increasing the nanoparticle load. This suggests that as particle load increases, the effect would not be an increasing disruption of the development of the κ-carrageenan network but rather an effect of higher local polysaccharide concentration in the interparticle space, due to the increasing total space occupied by the particle at higher loads. For higher loads of particles a stabilizing effect is observed and a gel network with intermediate strength is obtained.